Graphene quantum dot-decorated mesoporous silica nanoparticles for high aspirin loading capacity and its pH-triggered release. Issue 12 (9th March 2016) - Huang, Shaping; Song, Liping; Xiao, Zhidong; Hu, Yue; Peng, Meiwen; Li, Jinquan; Zheng, Xinsheng; Wu, Bin; Yuan, Chao
Abstract : In this paper, fluorescent graphene quantum dots (GQDs) grafted onto the surface of mesoporous silica nanoparticle (MSN) vehicles were prepared and characterized. Abstract : In this paper, fluorescent graphene quantum dots (GQDs) grafted onto the surface of mesoporous silica nanoparticle (MSN) vehicles were prepared and characterized. The as-prepared graphene quantum dot-decorated mesoporous silica nanoparticles (GQD-MSNs) exhibited excellent luminescence properties in vitro . Interestingly, compared to pure MSNs, the specific surface area and pore volume of GQD-MSNs increased by 59.1% and 48.9%, respectively. These optimized features granted GQD-MSNs a high aspirin loading capacity, which was twice as much as that of pure MSN. Moreover, most of the aspirin encapsulated (95.15%) could be released from the surface of GQD-MSNs under acidic conditions (pH 2.5) within 33 h.